2007
DOI: 10.1080/02688690701365770
|View full text |Cite
|
Sign up to set email alerts
|

Nocardia farcinicabrain abscess in a patient without immunocompromise

Abstract: Brain abscess has an incidence of 1 per 100,000 in developed countries and a mortality rate of 10%. Cerebral infections with Nocardia farcinica have a mortality of up to 90%. Nocardial species are important pathogens in immunocompromised hosts, but infections in immunocompetent patients are extremely rare. We report a case of primary brain abscess with N. farcinica in a patient without immunosuppression, which was treated with surgery and a one-year course of oral moxifloxacin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…BA occurs in 1/100,000 people annually in developed countries, and are more common in adult males [8,12] between 20 and 40 years old [3,6,17] and in children between 4 and 7 years old [7]. The incidence of this condition has grown as a consequence of increased numbers of immunocompromised patients [9].…”
Section: Introductionmentioning
confidence: 99%
“…BA occurs in 1/100,000 people annually in developed countries, and are more common in adult males [8,12] between 20 and 40 years old [3,6,17] and in children between 4 and 7 years old [7]. The incidence of this condition has grown as a consequence of increased numbers of immunocompromised patients [9].…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Nocardia brain abscess typically occurs in immunocompromised patients and less commonly in immunocompetent hosts. [12] We describe a case of an immunocompetent 34-year-old male with a Nocardia abscessus brain abscess and review similar reported cases in the literature.…”
Section: Introductionmentioning
confidence: 80%
“…Other cases of Nocardia farcinica brain abscess in immunocompetent patients have been reported in the literature [10], [13], [14], [15], [16]. Table 2 shows their treatments and outcomes.…”
Section: Discussionmentioning
confidence: 99%